(3eSGMI GdMdbs - (3CMeO Hf YeQ GdcQGHjSjs
(3ChdgG (B:s
(3aVd CMOi GdOGFQJjf GdeJhGRjJjf ai SWM Ydi GdGNQi GSei SWMkG eWhbkG s
(3BNQgG (B:s
(3eSGhjkG dfUa GdeMjW hfQSe KdK OhGjQ BNQ hjHjf GdeWdhH Ydi YcS GdfgL GdeJHY hgh GdeQGO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY YTQs
(3GfXQg eY GdeNWhW Qbe (B66 (3ef faS GdHYKIs
(3HgG CTcGd gfOSjIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(14/2432) s
Keywords: (3GdQjGVjGJs